Peran Pengawasan Internal Dalam Upaya Pencegahan Kecurangan Akuntansi Sektor Publik - Devi Savira; Sonny Fransisco Siboro; Shalshabila Shafa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Internal supervision plays a crucial role in preventing fraud that occurs in the public accounting sector (ASP) in Indonesia. Fraud is a serious problem that can harm various parties, both financially and in terms of reputation. This research technique reviews various aspects related to the internal supervision/control system, the role of internal audit, and other aspects or factors that contribute to efforts to prevent fraud. Through method techniques from a literature review, this study can be concluded, and analyze the results of related research, which highlights the importance of the whistleblowing system, implementation (e-procurement), and internal supervision/control system (SPI) as part of prevention strategy. The main findings show that internal control is very effective and significant in reducing the possibility of fraud. Meanwhile, a good internal supervision/control system (SPI) will play a very important role in protecting assets and maintaining the integrity of financial reports. The implications of this research objective can provide guidance for organizations to strengthen corporate financial governance and increase effectiveness in facing fraud challenges in the future.